Management Information System GIS : A tool for strategic decision - Romero B., Alfonso (2002)
The demand for emerging technology in making executive decisions , allows to have information systems that support this task from large volumes of information from management systems and integrated modern computer platform . The following article helps planning management information systems facilitating needed to reach such a global model integration and organization for overall management overview . The total management involves an integrated manner with control indicators since the birth of the business idea to the economic boom and the high altitude flight of profitability or industry manned by their managers and owners trying to keep the latter activity possible longer periods even if it has complied with the period of return on investment.